Nutritional Status Based on Four Anthropometric Indices and Associated Factors in Children between the Ages 0-2 Years Old in a Slum of Surabaya - Monica Tiara Arum Kinanthi; Mira Irmawati; Dwi Aprilawati (Faculty of Medicine Universitas Airlangga, 2021)
Introduction: Bulak Banteng sub-district is one of the slums in Surabaya. In a study in Bulak Banteng sub-district in 2015, 6.6% of children experienced malnutrition and 3% of children with Lower Red Line status. The highest number of children with Lower Red Line status was in RW 08. This study aimed to determine the nutritional status of children aged 0-2 years old in RW 08 Bulak Banteng sub-district, Surabaya, in 2018.Methods: This study used a cross-sectional descriptive study from primary data conducted by anthropometric measurement directly on toddlers and interviews with caregivers. Assessment of four anthropometric indices includes weight-for-age, height-for-age, weight-for-height, and head circumference-for-age. A sample of 50 toddlers was taken by proportional random sampling technique.Results: 31 children (62%) aged 0-2 years old in RW 08 Bulak Banteng sub-district had normal growth status based on weight-for-age, height-for-age, weight-for-height, and head circumference-for-age. The remaining growth status of 27 children (54%) is as follows. Based on the weight-for-age index, a child (2%) was severely underweight, and 7 children (14%) were underweight. Based on the height-for-age index, 4 children (8%) were severely stunted, and 7 children (14%) were stunted. Based on the index of weight-for-height, a child (2%) was severely wasted, and 5 children (10%) were wasted. Based on the index of head circumference-for-age, there were 1 child (2%) microcephaly and 3 children (6%) macrocephaly.Conclusion: This study found that many children aged 0-2 years old in the slum area of RW 08 Bulak Banteng sub-district in Surabaya experienced growth delays.